Simulation and analysis of HIV-AIDS dynamics. (27th December 2019) - Claver, Jimbo Henri; Pascal, Jesus; Mbassi, Achile; Foumane, Pascal
One of the most intriguing questions in mathematical epidemiology are how can one efficiently control and prevent the propagation of a disease. The problem of disease modelling, simulation and control becomes even more fascinating if we look at various risk groups. Referring to HIV-AIDS disease, it is worldwide agreed that the HIV virus seemingly knows when it should attack the body such as to develop AIDS disease. The fundamental question is therefore related to the time and location of such process to happen. To answer to this question, we study a model of propagation of HIV-AIDS in a given population. The AIDS disease is hardly easier to understand than HIV propagation dynamic, but fortunately, we can simplify the system even further by studying the susceptible and infected population dynamics in their behaviour in isolation and/or interaction. Finally, we develop a simulation model based on observed behaviours of susceptible and infected populations. This allows us to test our ideas of how the HIV virus develops into the AIDS disease within the highly controlled environment of computer simulation. Based on these insights, we can suggest new experiments on the actual system and update our models accordingly.